EVALUASI PEMBELAJARAN PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM TERHADAP PENILAIAN AKHIR SEMESTER - Tatang Muh Nasir Tatang Muh Nasir (Asaatidzah, 2022)
Through a literature study, this research tries to ascertain how well Islamic Religious Education (PAI) evaluates student learning outcomes. Evaluation is determined by using measurement information and assessment data. By using the Google form to provide a score (number) and the results are measured. The level of individual talent then determined by evaluating and interpreting the results according to certain standards. The results of this assessment process are also assessed to determine the level of achievement of individuals or programs. In general, there are two types of educational assessment methods: tests and non-tests. This study describes how the preparation of the instrument is based on the realm of cognitive, emotional, and psychomotor evaluation by using qualitative research findings using data or documents as sources. Validity, applicability, reliability, and economy are requirements for a solid set of tests and non-tests used to measure achievement. Item complexity or difficulty index, discriminating power, misleading analysis, item homogeneity analysis, and the efficiency of the choice function are also included in the analysis of appropriate tests for evaluating Islamic Religious Education (PAI) learning.